Social work in the criminal justice system: an ambiguous exercise of caring power - Svensson, Kerstin (Journal of Scandinavian studies in criminology and crime prevention, 2003)
In this article the caring power in the Swedish probation service is discussed. By exploring the history of probation, formed since the early 19 century, the structure that is constructed through human interaction and that defines the role of helper and helped is shown. Within this structure, different interpretations exist and different stories are told. This variation is highlighted through stories of support and control, told by social workers and clients. The purpose is to show that different aspects occur in different relationships, and that different discourses co-exist in a structure of caring power. Caring power is a way of exercising power through kindness. Support and control are different interpretations of the actions taken within the probation service and they are both part of the caring power. When the relationship between the social worker and the client is based on mutual understanding, the caring power can function and stories about the supportive aspects are told. When there is no mutual understanding, the actors tell stories about control. That way the caring power always exists, and depending on the relationship between the actors involved, we regard it in different ways. When the actors unite in their task, only the supportive aspects are shown, but when the actors cannot unite, the power is revealed